Canada's election: Harper's hour. (Economist, 2004)
According to an opinion poll conducted in June 2004, the Canadian Conservative party, under the leadership of Stephen Harper, could have enough support to form a minority government at the next general election on June 28. The poll suggested that the Conservatives now have 35 percent of the vote, as opposed to the ruling Liberals' 32 percent, which is a bitter blow to their prime minister, Paul Martin, who only recently spoke confidently of a ten-year reform program. Martin, who has been hit by scandal and dissatisfaction with his tax increases, is now looking to claw back the deficit during two public television debates before the election.